Mycorrhizal fungi and Fusarium species associated with vanilla in traditional management systems in Papantla, Veracruz, Mexico - Amanda Alejo-Viderique; María Del Pilar Ortega-Larrocea; Marcelo Rojas-Oropeza; Nathalie Cabirol (Botan‪ical Sciences, 2025)
Background: The Totonacapan region is recognized as the origin of vanilla cultivation (Vanilla planifolia Andrews), an orchid used for its gastronomic and medicinal values in rituals from pre-Hispanic times. Since that time, locals have cultivated vanilla using several traditional systems with different management practices. This plant forms symbiotic associations with mycorrhizal fungi inside its roots, which serve as a source of nutrients.